Assessment of Native Myocardial T1 Mapping for Early Detection of Anthracycline-Induced Cardiotoxicity in Patients with Cancer: a Systematic Review and Meta-analysis - Amira A. Mohamed (21841793) (2024)
Anthracycline antibiotic is one of the most effective anti-tumor drugs used to manage certain types of breast cancers, lymphomas, and leukemias. However, anthracyclines induce a dose-dependent cardiotoxicity that may progress to heart failure. Thus, using a sensitive predictor of early cardiac dysfunction in patients treated with anthracyclines can help detect subclinical cardiac dysfunction early and help initiate interventions to protect these patients. Among parameters of myocardial measure, cardiac magnetic resonance (CMR)-measured native myocardial T1 mapping is considered a sensitive and accurate quantitative measure of early subclinical cardiac changes, particularly cardiac inflammation and fibrosis. However, to understand the quality and the validity of the current evidence supporting the use of these measures in patients treated with anthracyclines, we aimed to conduct a systematic review of clinical studies of this measure to detect early myocardial changes in cancer patients treated with anthracyclines. The primary outcome was the level of native T1 mapping. We performed fixed-effects meta-analyses and assessed certainty in effect estimates. Of the 1780 publications reviewed (till 2022), 23 were retrieved, and 9 articles met the inclusion criteria. Our study showed that exposure to anthracycline was associated with a significant elevation of native myocardial T1 mapping from baseline (95% CI 0.1121 to 0.5802; p = 0.0037) as well as compared to healthy control patients (95% CI 0.2925 to 0.7448; p < 0.0001). No significant publication bias was noted on the assessment of the funnel plot and Egger’s test. According to the Q test, there was no significant heterogeneity in the included studies (I2 = 0.0000% versus healthy controls and I2 = 14.0666% versus baseline). Overall, our study suggests that native myocardial T1 mapping is useful for detecting anthracycline-induced cardiotoxicity in patients with cancer. Other Information Published in: Cardiovascular Toxicology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12012-024-09866-1